2022
DOI: 10.1155/2022/8661200
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of TNF-α-Mediated Accumulation of Phosphorylated Tau Protein and Its Modulation by Propofol in Primary Mouse Hippocampal Neurons: Role of Mitophagy, NLRP3, and p62/Keap1/Nrf2 Pathway

Abstract: Background. Neuroinflammation-induced phosphorylated Tau (p-Tau) deposition in central nervous system contributes to neurodegenerative disorders. Propofol possesses neuroprotective properties. We investigated its impacts on tumor necrosis factor-α (TNF-α)-mediated p-Tau deposition in neurons. Methods. Mouse hippocampal neurons were exposed to propofol followed by TNF-α. Cell viability, p-Tau, mitophagy, reactive oxygen species (ROS), NOD-like receptor protein 3 (NLRP3), antioxidant enzymes, and p62/Keap1/Nrf2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Akhtar et al stated that neuroinflammation was the core feature of neurodegeneration [ 2 ]. Moreover, TNF-α disrupted neuronal mitophagy, increased oxidative stress, triggered inflammation, dysregulated GSK-3 β activity, and promoted p-Tau accumulation [ 63 ]. Further, other studies stated that neurodegeneration in patients with T2DM could be considerably lowered by targeting cytokines, cytokine receptors, and nuclear transcription factors linked to inflammation, like IL-6 and TNF- α, alone or in combination [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akhtar et al stated that neuroinflammation was the core feature of neurodegeneration [ 2 ]. Moreover, TNF-α disrupted neuronal mitophagy, increased oxidative stress, triggered inflammation, dysregulated GSK-3 β activity, and promoted p-Tau accumulation [ 63 ]. Further, other studies stated that neurodegeneration in patients with T2DM could be considerably lowered by targeting cytokines, cytokine receptors, and nuclear transcription factors linked to inflammation, like IL-6 and TNF- α, alone or in combination [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Chen et al (2013) demonstrated that post-conditioning with propofol after hypoxia treatment can effectively inhibit H/R-induced apoptosis and autophagy in HUVECs by inhibiting PARP cleavage, up-regulating Bcl-2, down-regulating Bax, and preventing the transformation from LC3-I to LC3-II. Zhang et al (2022) also proved the neuroprotective properties of propofol. They found that propofol reduces neuronal damage caused by TNF-α-mediated p-tau deposition via knocking down p62, over-expressing Keap1, or inhibiting Nrf2 through p62/Keap1/Nrf2 pathway.…”
Section: Introductionmentioning
confidence: 81%